The informal sector wage gap: New evidence using quantile estimations on panel data - Olivier Bargain; Prudence Kwenda (University College Dublin, UCD School of Economics, 2009)
This paper provides new evidence on the wage gap between informal and formal salary workers in South Africa, Brazil and Mexico. We use rich datasets that allow us to define informality in a relatively comparable fashion across countries. We compute precise wage differentials by accounting for taxes paid in the formal sector. For each country, we analyze how the sectoral wage gap varies within groups, between groups and over time. To account for unobserved heterogeneity, we use large (unbalanced) panels to estimate fixed effects models at the mean and at different points of the wage distribution. We find that unobserved heterogeneity explains a large part of the (conditional) wage gap. The remaining informal sector wage penalty is large in the lower part of the distribution but almost disappears at the top. The penalty primarily concerns young workers and is found to be procyclical. We carefully investigate the robustness of these results and discuss their policy implications as well as regularities across countries.
hdl:10197/2601
Keywords: J21; J23; J24; J31; C14; O17; 330; Wage gap; Informal sector; Quantile regression; Fixed effects model; Selection